The role human resource management in the reorganizing of development of health sector and an application - Gürkan, Özlem (My University, 2006)
Bu tez çalışmasında, yeniden yapılanma, amaçları, uygulanması, insan kaynakları yönetiminin bu süreçteki rolü ve uygulama örneği olarak seçilen sağlık işletmeleri, karakteristikleri ve tarihsel gelişimleri incelenmiştir. Sağlık işletmeleri dinamik çevre koşullarında ayakta kalabilmek için, değişimi ve örgütün buna uyumunu sağlamalıdır. Sağlık sektöründe kurumsallaşmayla birlikte insan kaynakları departmanı da örgüt şemasında yerini almaktadır. Söz konusu uyumu sağlama ve yeniden yapılanmanın başarılı bir şekilde sonuçlanmasında örgütün tümüne etki eden ve stratejik bir noktada bulunan insan kaynakları yönetiminin önemi büyüktür

In this thesis study, reorganization, the purpose of reorganization, implementation and the role of human resource management during this process and chosen as an application area, also health organizations, their characteristics, historical development have been analyzed. Health organizations also have to support change and harmonization of the organization with the changes, in order to be able to stand against dynamic environmental conditions. Within institutionalization and reorganizing process, human resource department has taken important place in the organization chart. Human resource management, which has direct effects on entire organization, is at a strategic position in providing the mentioned harmonization and a successful compilation of reorganization.
Keywords: İnsan Kaynakları Yönetimi; Yeniden Yapılanma (Yönetim)